Indigenous Principals' Perspectives on Leadership Development - Scott, D.; Scott, Shelleyann; Dixon, Kathryn; Okoko, J.; Dixon, Robert (Emerald Insight, 2014)
This chapter presents a cross-cultural comparison across the Commonwealth, namely, Australia, Canada, and Kenya. The three cases explore these indigenous principals’ perceptions of leadership development and how effectively these experiences prepared them to meet the challenges within their complex school communities. The chapter presents a discussion of the historical educational legacies of imperial rule, leadership preparation opportunities that were available to aspiring and novice leaders, the challenges the principals encountered in their leadership role in the school and within their communities, and these leaders’ beliefs and attitudes toward leadership. A final synthesis is presented, which identifies a number of commonalities in leadership approaches across these very different cultural contexts: the school communities were endeavoring to rediscover their cultural history, heritage, and beliefs and were frequently developing positive relationships with elders and others who held, and were willing to pass on, the historical and cultural knowledge and expertise. The leaders themselves held strong beliefs about the importance of cultural identity in order to forge new and contemporary pathways to success for their students. They all had a heightened ethic of care ethos that extended beyond the confines of the school building and office hours. These leaders adopted entrepreneurial leadership approaches to think and act innovatively rather than simply managing schools and were dedicated to promoting educational success for all students within their care. Leadership development implications included the need for formal, informal, and experiential experiences, as well as, for the inclusion of specific knowledge and skills that would enable leaders to effectively and sensitively lead within predominantly indigenous school communities.